EMPOWERING FAMILY WELFARE AND MEMBERS THROUGH BLENDED LEARNING TRAINING AND DIGITAL APPLICATION UTILIZATION FOR HOME-BASED ENGLISH LEARNING ASSISTANCE - Ch. Evy Tri Widyahening; Luqman Al Hakim (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
This article discusses a community service program focused on introducing the concept of blended learning and its implementation in English language learning for members of the family welfare and empowering the RW 01 community organization in Sangkrah Village, Pasar Kliwon District, Surakarta. The program aimed to introduce blended learning as a flexible and effective instructional model to enhance participants' English language proficiency. The methods employed included interactive lectures, video presentations on blended learning, group discussions, and simulations of technology-assisted learning. Throughout the program, participants were encouraged to identify the characteristics and practical applications of blended learning in educational settings. The results indicated that participants developed a better understanding of the blended learning concept and demonstrated increased motivation to learn English. Furthermore, they were able to utilize supporting technologies, such as smartphones and learning applications, to facilitate a more flexible, effective, and engaging English learning experience. This program is expected to serve as an initial step toward improving digital literacy and English language proficiency among fam?ly welfare and empowerment members while providing an example of an innovative learning model that can be adapted to various community-based educational activities.